BECK MERCHANT’S REVENGE AS REFLECTED IN SANDRA BROWN’S WHITE HOT: A PSYCHOSOCIAL STUDY - Fitri Palupi (Premise: Journal of English Education and Applied Linguistics, 2012)
The White Hot is the novel from American writer. She is Sandra Brown, was born in Waco on March 12 1948. She began her writing carrier in 1981, since then she has published 68 novels. White hot was released in August of 2004 and became the best seller novel in many bookstores. This novel tells much about revenge, where revenge becomes phenomenon that booming in our daily life. It describes Beck Merchant as the protagonist who had a motive to seek revenge. This research entitled “Beck Merchant’s revenge as reflected in Sandra Brown’s white Hot: A Psychosocial Study” is intended 1) to describe the motives of seeking revenge of Beck Merchant in the novel White Hot 2) to describe the way how Beck Merchant solve his problems.The type of this research is a library research. The researcher uses the primary data and secondary data. The primary data is the novel White Hot written by Sandra Brown. With the primary data, the researcher reads and observes the novel White Hot carefully and critically. The secondary data of the research are taken from other sources such as some critical books from the library and also data from internet are used to help the researcher to interpret the novel White Hot. The data analysis technique used in this research is descriptive qualitative method. In doing this research the writer uses psychoanalysis theory by Sigmund Freud. It is the theory which analyzes Beck Merchant’s revenge related to Id, Ego and Superego.